Development, Validity and Reliability of Objective Structured Clinical Examination in Nursing Students - Carolina Chabrera; Eva Diago; Laura Curell (SAGE Publishing, 2023)
Introduction The adoption of measurement instruments such as the Objective Structured Clinical Examination (OSCE) is essential to assess clinical competencies in nursing students. Objective The purpose of this study is to develop an OSCE, analyze its validity and reliability in the nursing curriculum and measure self-assessment, stress and satisfaction. Methods The observational validation study of a measurement instrument was carried out in two phases: the design and development of the OSCE and validity and reliability analysis. Results A total of 118 students participated in the study. Ten scenarios were designed that incorporated six competency components extracted from the curriculum. Good results were obtained in face validity, content validity (CVI .82-.95), criterion validity (r = .71, p < .001), and reliability (α Cronbach .84). Satisfaction and stress scores were high, and self-assessment scores were lower than the scores obtained. Conclusion A rigorously designed OSCE provides a reliable and valid method for assessing the clinical competence of nursing students.